Automatic recognition of type III solar radio bursts in STEREO/WAVES data for onboard real‐time and archived data processing. Issue 2 (14th February 2014) - Lobzin, V. V.; Cairns, Iver H.; Zaslavsky, A.
<x xml:space="preserve">Abstract</x> Type III radio bursts are produced near the local electron plasma frequency and/or near its harmonic by fast electrons ejected from the solar active regions and moving through the corona and solar wind. These bursts have dynamic spectra with frequency rapidly falling with time. This paper presents two new methods developed to detect type III bursts automatically in the data from High Frequency Receiver (HFR) of the STEREO/WAVES radio instrument onboard the STEREO spacecraft. The first technique is applicable to the low‐frequency band (HFR‐1: 125 kHz to 1.975 MHz) only. This technique can possibly be implemented in onboard satellite software aimed at preliminary detection of bursts and identification of time intervals with relatively high solar activity. In the second technique the bursts are detected in both the low‐frequency band and the high‐frequency band (HFR‐2: 2.025 MHz to 16.025 MHz), with the computational burden being higher by 1 order of magnitude as compared with that for the first technique. Preliminary tests of the method show that the performance of the first technique is quite high, PdL=72%±3%. The performance of the second technique is considerably higher, PdL+H=81%±1%, while the number of false alarms does not exceed 10% for one daily spectrum.